Measuring morphological canonicity - Walther, Géraldine (Linguistica (Ljubljana), 2011)
The question of regularity within morphological paradigms has been formerly addressed within approaches falling in the scope of Canonical Typology (Corbett 2003). The aim of this paper is to provide a means for assessing the notion of morphological canonicity through original measures developed within our new morphological framework PARSLI. In particular, we introduce original measures for non-canonical phenomena such as heteroclisis, deponency, defectiveness and overabundance. We introduce PARSLI a new model for inflectional morphology using an inferential-realisational approach (Matthews 1974; Zwicky 1985; Anderson 1992). Our model precisely provides a formal representation of the lexicon/grammar interface. It relies on a formal definition of a lexical entry and a complete formal apparatus for computing all relevant form realisation rules for each lexeme, including stem formation rules. Realisation rules themselves may be expressed through any suitable realisation-based formalism (e.g. PFM or Network Morphology). We introduce several formal innovations such as inflection zones, that constitute partitions of given inflection classes. They are in particular used in modelling heteroclisis.
Keywords: morfologija; morphologie; morphologie canonique; oblikoslovje; oblikoslovna kanoničnost; oblikoslovni model "parsli"; PARSLI